Statistical models in population genetics - Hobolth, Asger (Henry Stewart Talks, 2016)
The site frequency spectrum (SFS), Wright-Fisher with no mutations, The coalescent process (backwards Wright-Fisher), Adding mutations, The expected SFS, Distance between heterozygote sites, Wright-Fisher with recombination, The ancestral recombination graph (ARG), Probability tree heights along the sequence, Expected histogram for distance between heterozygote sites, Simulation study: detecting a bottleneck